Kepemimpinan, Kompensasi, Kompetensi dan Kinerja Karyawan : Peran Mediasi Motivasi - Leonardus Teguh Handoyo; Suryatunnisak Suryatunnisak; Legia Seki Yolanda; Lingga Ramadhana Arfi (Program Pascasarjana STIE Amkop Makassar, 2026)
Low employee performance is one of the key determinants of an organization’s success in achieving its goals. This phenomenon is also experienced by PT. Cahaya Riau, where leadership and competence are believed to influence employee performance, and employee motivation is also suspected to act as a mediating factor. This study aims to examine the influence of leadership, compensation, and competence on employee motivation and performance at PT. Cahaya Riau. This study utilizes primary data obtained from a questionnaire administered to employees of PT. Cahaya Riau. Secondary data from the company includes employee records, salary information, training records, and organizational structure. The sample size for this study is 112 individuals, selected using simple random sampling. The analysis method used is Path Analysis with the assistance of the SPSS program. The results of the study indicate that 1) Leadership has a positive and significant effect on performance, 2) Compensation has a positive and significant effect on performance, 3) Competence has a positive and significant effect on performance, 4) Motivation has a positive and significant effect on performance, 5) Leadership influences performance through motivation, 6) Compensation influences performance through motivation, and 7) Competence influences performance through motivation.